PERANCANGAN GAME "YUK, SUKSES UN!" SEBAGAI MEDIA PEMBELAJARAN PARA SISWA DALAM PERANGKAT SMARTPHONE - Godham Eko Saputro (DeKaVe, 2013)
Games are entertainment media with the highest growth among other smartphone features suchas music, Tv, and movies. Besides having a huge potential in the field of economic and entertainment, thegame also has the potentia/field of instructional media. The students assume the National Examinationas a fear factor can utilize the smartphone as a learning medium, especially students who come from ruralareas who have difficulty in accessing the textbook exercises.By utilizing the game functions as a medium of learning the game design " Yuk, UNSuccess! " In the android operating system which includes a question bank content package, asummary of the material, the lattice, and the discussion of the UN is expected to increase the graduationrate of students nationallyKeywords: Game, Medium of/earning, Android.